Minding the Gap: Networks of Animal Welfare Service Provision. (July 2017) - Reese, Laura A.; Ye, Minting
This research focuses on public service provision in the context of an important emerging urban policy issue: increasing numbers of roaming animals in distressed cities in the United States. The case of urban animal welfare policy illustrates a policy domain that relies heavily on informal networks of nonprofit organizations for service provision. How these networks function and the interaction between nonprofit and public entities says much about how cities will be able to respond to increasingly changing policy environments. Based on survey and network analysis of organizations involved in animal welfare service provision in Detroit, the following conclusions are drawn: Urban animal welfare services are much broader than simple animal "control" and encompass the physical, behavioral, and emotional well-being of animals; less common aspects of animal welfare services evidence the highest levels of cooperation; a fragmented network of nonprofit rescues and public entities is providing animal welfare services in the City of Detroit although nonprofit providers dominate; and collaborative service networks vary greatly in size, density, and composition depending on different aspects of services provided.